2015
DOI: 10.1111/1440-1681.12501
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclooxygenase‐1 and ‐2 in endothelium‐dependent contraction of atherosclerotic mouse abdominal aortas

Abstract: The objective of this study was to determine the role of cyclooxygenase (COX)-1 or -2 in endothelium-dependent contraction under atherosclerotic conditions. Atherosclerosis was induced in apoE knockout (apoE(-/-)) mice and those with COX-1(-/-) (apoE(-/-)-COX-1(-/-)) by feeding with high fat and cholesterol food. Aortas (abdominal or the whole section) were isolated for functional and/or biochemical analyses. As in non-atherosclerotic conditions, the muscarinic receptor agonist acetylcholine (ACh) evoked an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 55 publications
4
39
0
Order By: Relevance
“…3), we observed that Cox-1 prevails over Cox-2 in the mediation of the endothelium-dependent vasoconstrictor response to PE apoE -/- mice. This is in agreement with the finding that aortic endothelial cells preferentially express Cox-1 versus Cox-2 [31, 41], and that as Cox-1 expression is increased, the major source of vasoconstrictor prostanoids is converted into the endothelial cells, which diffuse to contract the underlying vascular smooth muscle in arteries of mouse models of cardiovascular diseases [31, 42]. Importantly, chronic treatment with sildenafil normalized the vascular hypercontractility (R max ) in this model of AT.…”
Section: Discussionsupporting
confidence: 92%
“…3), we observed that Cox-1 prevails over Cox-2 in the mediation of the endothelium-dependent vasoconstrictor response to PE apoE -/- mice. This is in agreement with the finding that aortic endothelial cells preferentially express Cox-1 versus Cox-2 [31, 41], and that as Cox-1 expression is increased, the major source of vasoconstrictor prostanoids is converted into the endothelial cells, which diffuse to contract the underlying vascular smooth muscle in arteries of mouse models of cardiovascular diseases [31, 42]. Importantly, chronic treatment with sildenafil normalized the vascular hypercontractility (R max ) in this model of AT.…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies showed that COX-derived products do not contribute to vasodilation in healthy resistance vessels in rodents 14 but are implicated in conduit vessel function in the setting of obesity and dyslipidemia. 30,37 We found that indomethacin does not affect acetylcholine-induced relaxation at baseline in small mesenteric resistance arteries or in mice exposed to risk factors regardless of their sex or the presence of EC-MR ( Figure 3). These data suggest that COX-derived products do not contribute to endothelium-dependent relaxation in mesenteric resistance microvessels in these obesity and hyperlipidemia models.…”
Section: Sex Differences In the Contributions Of No And Edh To Microvmentioning
confidence: 90%
“…Thus, while its blood level could be lower than that of our in vivo studies, the amount of PGE 2 produced inside the vascular wall could easily reach a level (eg, the amount of PGE 2 produced in ACh-stimulated atherosclerotic mouse abdominal aorta is ~0.5 ng/mg or 1.35 μmol/kg tissue) required for activations of both EP3 (from ≤0.001 μM) and TP to regulate local vascular function or to buffer its general dilator effect systemically. 40 Furthermore, the unaltered maximal contraction in EP3 −/− arteries implies that the effect of PGE 2 via TP is more efficacious than that via EP3, explaining why PGE 2 evokes contraction at higher concentrations even in vessels where it initially elicits relaxation. 18,25 Meanwhile, the difference in effects between EP4 and EP2 antagonisms and that in mRNA expressions could be explained by EP4's mediating the vasodilator effect of PGE 2 on the renal vasculature 13,24,25 and the unintended effects that might be associated with prostanoid receptor antagonists.…”
Section: Influences Of Tp −/− And/or Ep3 −/− On Expressions or Funcmentioning
confidence: 99%